TEACHING DESCRIPTIVE WRITING BY USING CUBING STRATEGY TO THE EIGHTH GRADE STUDENTS OF SMP N 22 PALEMBANG - jhonni iskandar (Edukasi, 2017)
The objectives of the study are to find out whether or not there is a significant improvement on the eighth grade students’ descriptive writing achievement who are taught by using Cubing strategy at SMP N 22 Palembang and to find out whether or not there is a significant difference between the eighth grade student’s descriptive writing achievement between those who are taught by using Cubing strategy and those who are not at SMP N 22 Palembang. The population of this study consisted of 230 eighth grade students of SMPN 22 Palembang. The sample of this study was taken by using purposive sampling. There were 62 students taken as sample. Each class consisted of 31 students from class VIII 3 as control group and class VIII 6 as experimental group. This sudy used quasi experimental design. The instrument used in collecting data was writing test. The test was administered twice, as a pre-test and post-test for both control and experimental groups. The result of the test were analyzed by using SPSS 16. The data of pretest and posttest of the experimental and control groups were analyzed by using independent sample t-test and paired sample t-test in SPSS program. The findings showed that the p-output from paired sample t-test (sig2-tailed) was 0.000 which was lower than 0.05 and the t-value (11.020) was higher than t-table with df=30 (2,0423). P-output from independent sample t-test was 0.000 which was lower than 0.05 and the t-value (8.827) was higher than t-table with df=60 (2,0003 ). It means that there was a significant difference on the eighth grade students at SMP N 22 Palembang who are taught by using Cubing Strategy.